Gravel Replenishment Downstream of Dams: Insights From a Flume Experiment in a Straight Embanked Channel - Junjian Deng; Guillaume Brousse; Magali Jodeau (Water Resources Research, 2025)
Abstract Gravel replenishment (GR) is a common strategy to mitigate the negative effects of sediment deficit caused by dam regulation. However, its effectiveness in restoring dam‐regulated embanked gravel‐bed rivers with alternate bars is still unclear. It is of particular interest to understand how bar morphology evolves under GR and how replenished channel's response varies according to the presence or absence of upstream sediment supply, which is often controlled by dams. We conducted a laboratory experiment to investigate the morphological effects of a single high‐flow stockpile replenishment in a straight embanked channel with steady hybrid bars. Two floods with and without upstream sediment supply, respectively were introduced in the flume, each followed by moderate flow. A stockpile with the same volume was added to the flume before each flood. Results showed that lateral erosion of the stockpile was strongest when upstream sediment supply was maintained, while the sediment wave propagated further when sediment supply was eliminated. Topographic data showed bar suppression triggered by stockpile regardless of upstream sediment supply during the flood. After the flood, bar morphology reappeared with maintained upstream sediment supply, while a single‐thread incised channel was observed at the end of the scenario without upstream supply. These observations suggest that sediment replenishment, combined with controlled flow and sediment releases from the dam, can strongly modify bar morphology of an embanked river. The magnitude and type of river morphology changes also depend on upstream dam operations at high flow.